1987
DOI: 10.1161/01.hyp.10.2.212
|View full text |Cite
|
Sign up to set email alerts
|

Renal scintigraphic captopril test in the diagnosis of renovascular hypertension.

Abstract: SUMMARY Angiotensin converting enzyme (ACE) inhibitor-induced renal failure has been reported in bilateral renal artery stenosis and in stenosis in solitary kidneys, but not in unilateral renal artery stenosis. In these patients, however, a functional impairment of the kidney ipsilateral to the stenosis can often be detected after ACE inhibition by scintigraphic techniques employing glomerular radionuclide tracers like 99n> Tc-diethylenetriamine pentaacetic acid (DTPA). Dynamic renal scintigraphy with "Tc-DTPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…Since the first reports on captopril-enhanced scintigra phy showing a sensitivity over 80% and a specificity close to 100% [17,18], the possibility of false-negative results in patients with very small ischemic kidneys and false positive results in cases of chronic renal parenchymal dis ease was widely recognized and the opportunity of an extensive study on a large series of patients was thought to be needed in order to justify the use of captopril-enhanced scintigraphy as first procedure in noninvasive screening test for RVH. Our results confirm, in a sample of 667 a priori unselected patients, that captopril-enhanced scin tigraphy is a reliable test, noninvasive, feasible even in high-risk patients, free of the nephrotoxic effects of the diagnostic procedures employing contrast media and that it has a definite role in the diagnostic screening of hyper tensive patients even in cases with preexisting renal im pairment, in which sensitivity and specificity have been a matter of debate [19], When a diagnosis of RAS is made, the fundamental problem is to discriminate between RAS coexistent with essential hypertension and RVH.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first reports on captopril-enhanced scintigra phy showing a sensitivity over 80% and a specificity close to 100% [17,18], the possibility of false-negative results in patients with very small ischemic kidneys and false positive results in cases of chronic renal parenchymal dis ease was widely recognized and the opportunity of an extensive study on a large series of patients was thought to be needed in order to justify the use of captopril-enhanced scintigraphy as first procedure in noninvasive screening test for RVH. Our results confirm, in a sample of 667 a priori unselected patients, that captopril-enhanced scin tigraphy is a reliable test, noninvasive, feasible even in high-risk patients, free of the nephrotoxic effects of the diagnostic procedures employing contrast media and that it has a definite role in the diagnostic screening of hyper tensive patients even in cases with preexisting renal im pairment, in which sensitivity and specificity have been a matter of debate [19], When a diagnosis of RAS is made, the fundamental problem is to discriminate between RAS coexistent with essential hypertension and RVH.…”
Section: Discussionmentioning
confidence: 99%
“…24 Fommei E at al (1987) reported positive captopril induced changes in Tc99m-DTPA scintigraphy which predicted patients who can be cured by revascularization or percutaneous transfemoral renal angioplasty (PTRA). 25 Mann S J et al (1991) compared usefulness of 131 I-OIH scintigraphy to be more accurate than Tc99m-DTPA. 26 captopril renal scintigraphy in RVH and showed that positive preoperative renal scintigraphy in strong predictor of hypertension curability of revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…This is reversible, as is the acute rise in plasma creatinine that accompanies administration of ACE inhibitors to patients with renovascular hyperten sion. This change in the isotopic renogram following captopril administration, together with the rise in plasma renin, can be used diagnostically to confirm renovascular hypertension [15],…”
Section: Overviewmentioning
confidence: 99%